2013
DOI: 10.1080/00140139.2012.751458
|View full text |Cite
|
Sign up to set email alerts
|

To twist, roll, stroke or poke? A study of input devices for menu navigation in the cockpit

Abstract: This study evaluated four input devices for control of a screen-based flight management system. A holistic approach was used to evaluate both cognitive and physical performance. Performance varied across the dependent variables and between the devices; however, the touch screen produced the largest number of 'best' scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…Authors concluded that touch screens help pilots to keep their attention, reduce cognitive effort, search time, and motor movement. A similar study was conducted by Stanton et al [5] which confirmed these findings. However, subjective impressions revealed an increased discomfort compared to other input devices.…”
Section: Introductionsupporting
confidence: 81%
“…Authors concluded that touch screens help pilots to keep their attention, reduce cognitive effort, search time, and motor movement. A similar study was conducted by Stanton et al [5] which confirmed these findings. However, subjective impressions revealed an increased discomfort compared to other input devices.…”
Section: Introductionsupporting
confidence: 81%
“…Several empirical studies have suggested that incorporating touchscreens into the cockpit environment could offer advantages over other input devices. Stanton et al (2013) examined the comparative performance of four different types of input device (trackball, rotary controller, touchpad and touchscreen) for in-flight menu navigation, concluding that the touchscreen offered the best overall performance across a variety of measures. Thomas (2017) recently analysed pointing performance using a Fitts' Law methodology, comparing a hand-on-throttle-and-stick (HOTAS) isotonic pointing fingerstick with three input devicestrackball, trackpad, and touchscreen.…”
Section: Cockpit Touchscreen Interactionmentioning
confidence: 99%
“…Previous studies have found that fixed touchscreen use tends to be more physically demanding and lead to more bodily discomfort (Stanton et al 2013;Harvey et al 2011) and suffer from higher error rates (Avsar, Fischer andRodden 2015, Cockburn et al, 2017) than other input devices such as trackballs and touchpads (Lin et al, 2010;Yau, Chao andHwang, 2008, Cockburn et al, 2017). However despite this, in a flight deck context, for all vibration conditions, the usability and workload appeared comparable to those reported from other input devices, for both the centre and side screens.…”
Section: Discussionmentioning
confidence: 99%
“…aircraft, robotics or cycling); aircraft being categorized under other environments as only two papers were identified in this domain. These identified that the use of touchscreens in the cockpit can improve performance when compared with trackball inputs (Eichinger & Kellerer, 2014) as well as rotary controllers and touch pads (Stanton et al, 2013), however as only static conditions were investigated, these findings may not apply for non-static conditions. Touchscreens were also found to be more usable by those engaging with them in simulated cockpit environments when compared to alternative inputs (Stanton et al, 2013).…”
Section: Introductionmentioning
confidence: 99%